Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi - Fenty Y Manuhuttu; Agung Saputra Agung (Faculty Of Economics and Business, Musamus University, 2023)
This research aims to find out how much influence the variables government spending and exports have on economic growth in 2013-2022. Research is limited to analyzing annual secondary data in 2013-2022. The data is analyzed using quantitative methods, and the technique used is multiple linear regression analysis. With the help of SPSS 21, The effect of government spending on economic growth based on the study shows that the hypothesis is accepted where the table count and graph value are 0.001 <0.05, and the coefficient value is 1.045. Thus, government spending has a positive and significant effect on economic growth. This means that government spending has increased by 1%, which means economic growth will increase by 1.045. And conversely, if government spending decreases, economic growth will also decrease by 1.045. Based on the analysis results, the value of exports on economic growth can be seen from the accepted hypothesis where the table calculation and significance value is 0.009<0.05, and the coefficient value is 0.094. Thus, exports have a positive and significant effect on economic growth. This means that if exports experience an increase of 1%, economic growth will experience an increase of 0.094. And conversely, if exports experience a decrease, economic growth will also experience a decrease of 0.094. Simultaneously, government spending and exports positively influence economic growth in Papua Province. Keywords: Economic Growth, Population Growth and Unemployment Rate